The Effects of Institutional Ownership, Managerial Ownership, Audit Committee, Gender Diversity, and Profitability on Carbon Emissions Disclosure - Shafira Syauqina Munifah; Erma Setiawati (Golden Ratio of Auditing Research, 2027)
This study aims to analyze the effects of institutional ownership, managerial ownership, audit committee, gender diversity, and profitability on carbon emission disclosure in non-financial companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study uses secondary data obtained from annual reports and sustainability reports published by companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling, resulting in a total sample of 56 companies with 224 firm-year observations over a four-year period. The dependent variable in this study is carbon emission disclosure, measured using the Carbon Emission Disclosure (CED) Index. The independent variables include institutional ownership, managerial ownership, audit committee, gender diversity, and profitability. The data analysis method used is multiple linear regression analysis, and the data have passed the classical assumption tests. The results indicate that institutional ownership, managerial ownership, and gender diversity have a negative and significant effect on carbon emission disclosure. Meanwhile, audit committee and profitability do not have a significant effect on carbon emission disclosure.